2021
DOI: 10.1111/ajo.13457
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of maternal near miss assessment in Australia, New Zealand, South‐East Asia and the South Pacific region: How, what, why and where to?

Abstract: Background: Severe maternal morbidity or maternal near miss (MNM) events can have significant consequences for individuals, their families and society and the study of these events may inform practices to reduce future adverse pregnancy outcomes. Aims:To review the scope of MNM studies undertaken in Australia, New Zealand, South-East Asia and the South Pacific region. Materials and Methods:A systematic search of four online databases (MEDLINE, EMBASE, SCOPUS and CINAHL) and the World Health Organization Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 90 publications
(242 reference statements)
0
7
0
Order By: Relevance
“…The literature describes various methods for investigating SAMM in Australia, including: prospective cross-sectional studies, 14 retrospective cohort studies collated using administrative and population health datasets, 14,15 and condition-specific registries. 16 A voluntary national reporting system, The Australasian Maternity Outcomes Surveillance System (AMOSS), was used to research selected rare and serious conditions in pregnancy 16 (details in Table 1).…”
Section: Recording: Data Collection Methodsmentioning
confidence: 99%
“…The literature describes various methods for investigating SAMM in Australia, including: prospective cross-sectional studies, 14 retrospective cohort studies collated using administrative and population health datasets, 14,15 and condition-specific registries. 16 A voluntary national reporting system, The Australasian Maternity Outcomes Surveillance System (AMOSS), was used to research selected rare and serious conditions in pregnancy 16 (details in Table 1).…”
Section: Recording: Data Collection Methodsmentioning
confidence: 99%
“…12,13 The causes of the majority of SMM globally are sepsis, haemorrhage (usually postpartum haemorrhage), hypertensive disorders, mainly preeclampsia and eclampsia, and pre-existing co-morbidities such as cardiovascular disease and the management of these disease processes. 14 Different jurisdictions have shown that between 30 and 60% of SMM is preventable and that the commonest factors are provider (clinician) or system-related rather than being related to the pregnant person or their family. 2,14,15 Related to SMM, within-country inequities must be highlighted to show how maternity care systems might be privileging whiteness.…”
mentioning
confidence: 99%
“…14 Different jurisdictions have shown that between 30 and 60% of SMM is preventable and that the commonest factors are provider (clinician) or system-related rather than being related to the pregnant person or their family. 2,14,15 Related to SMM, within-country inequities must be highlighted to show how maternity care systems might be privileging whiteness. 16 Non-Hispanic Black American women suffer much higher rates of SMM than non-Hispanic Whites in the USA.…”
mentioning
confidence: 99%
See 2 more Smart Citations